The Use Of Quizizz Application To Increase Descriptive Text Writing Skills Of Eleventh Grade Students - Anggreni Nurmika Turnip; Mungkap Mangapul Siahaan; Partohap Saut Raja Sihombing (STABN RADEN WIJAYA WONOGIRI, 2022)
Writing skills are one of the essential skills in learning English. However, many students have difficulty developing ideas, using appropriate vocabulary, and structuring sentences into well-organized paragraphs, especially when writing descriptive texts. This research aims to investigate the effect of using the Quizizz Application on students’ writing skills, particularly in writing descriptive texts. This research uses a quantitative method with a quasi-experimental design. The population of this research was eleventh grade students at SMA Negeri 5 Pematangsiantar, and two classes were selected as samples using purposive sampling. The experimental class (XI-4) consisted of 33 students who were taught using the Quizizz Application, while the control class (XI-1) consisted of 33 students who were taught using the conventional model. Data were collected through pre-test and post-test writing assignments, then analyzed using an independent sample test. The results showed that the average score of the experimental class increased from 53,70 on the pre-test to 84,16 on the post-test, while the control class increased from 43,37 on the pre-test to 59,67 on the post-test. Statistical analysis showed that the significance value was 0.000 < 0.05, which means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This means that there was a significant improvement in students in the experimental class who received the treatment. Thus, this shows that there is a significant difference between the experimental class and the control class. Therefore, the use of the Quizizz Application has a positive and significant effect on students’ writing skills in descriptive texts. Based on these findings, Quizizz can be used as an effective and interactive learning medium to improve students’ writing skills.